Adolescência heteronormativa masculina: entre a construção obrigatória e a desconstrução necessária - Santos, Welson Barbosa (2015)
The purpose of this thesis is to contribute to the edification of knowledge concerning the construction of youth masculinity. The hypothesis is that heterosexuality needs homosexuality for its own strengthening and that by accusing, signaling and judging the "less" or non-hegemonic male, or the homosexual, it reinforces itself. Established by cultural experiences, masculinity is built through social relationships and communication in places such as school and the internet. So, to connect both of these spaces methodologically, the study initially includes 600 subjects, both male and female, of two educational institutions in the municipal of Uberaba-MG, Brazil. From this particular group only 200 males, between ages 14 to 16, were identified and invited to continue taking part in the study. The students were asked several objective questions which led to the identification of 17 out of the 200 subjects. The use of communication through social networks with the identified males allowed for the observation of their speech and expressions, which has been used as reinforcement and reference for this discussion. So referenced, conceivable understandings of social components and procedures of the formation of male adolescents’ identity and the independence between each category have risen. Furthermore this thesis attempts to contribute to the understanding of how masculinities in adolescence are determined, experienced and inherited